INVESTIGATIONS OF GAS-SENSITIVE NANOSIZE ZnO < Al > FILMS - V. Arakelyan; V. E. Galstyan; G. Shahnazaryan
Nanosize ZnO < Al > thin films have been manufactured on glassceramic substrates by the magnetron sputtering method. It is shown that this structure can be used in manufacturing of single-hydrogen sensors and “electronic nose” as well.
Keywords: Physics; Electronic structure and electrical properties of surfaces